Pengaruh Kekayaan Daerah dan Belanja Daerah terhadap Pengungkapan Internet Financial Reporting (IFR) pada Pemerintah Daerah - Widya Putri; Mia Angelina Setiawan (Jurnal Eksplorasi Akuntansi, 2022)
This study is a quantitative study that aims to obtain empirical evidence regarding the influence of regional wealth and regional expenditure on the disclosure of Internet Financial Reporting (IFR) in local governments. The population in this study is the district/city government in West Sumatra Province for the period 2018-2020 for 3 years. This study uses purposive sampling method in selecting the sample, with a sample size of 19 districts/cities in West Sumatra Province. The type of data in this study is secondary data obtained from BPK. Analysis of the data used is multiple regression analysis. The results of this study indicate that regional wealth has no effect on IFR disclosure, and regional expenditures have a negative and significant effect on IFR disclosure.